Effects of Sodium Chloride and Sodium Sulphate Solutions on the Output of the Electrochemical Machining - qasim, heba saad; Aghdeab, Shukry H. (Al-Khwarizmi Engineering Journal, 2019)
Electrochemical Machining is a term given to one of nontraditional machining that uses a chemical reaction associated with electric current to remove the material. The process is depending on the principle of anodic dissolution theory for evaluating material removal during electrochemical process. In this study, the electrochemical machining was used to remove 1 mm from the length of the a workpiece (stainless steel 316 H) by immersing it in to electrolyte (10, 20 and 30 g) of NaCl and Na2SO4 to every (1 litter of filtered water).  The tool used was made from copper. Gap size between the workpiece and electrode is (0.5) mm. This study focuses on the effect of the changing the type and concentration of electrolyte solution, the effect of the value of current (2, 5 and 10) A and the effect of the value of the voltage (6, 12 and 20)V on the Surface Roughness (Ra) and Material Removal Rate (MRR) of the workpiece. The results of comparison of experimental showed that (Na2SO4) solution give surface roughness less than (NaCl) solution in all levels, maximum (Ra) is (0.658) and minimum (0.420), while (NaCl) solution give maximum (Ra) is (2.913) and minimum is (0.508), also give (MRR) higher from (NaCl) solution in level (30 g/l ) at (5 A) , (10 and 20 g/l) at (10 A) ,and (30)g/l at (6 &12 V). This study aims to compare the effect of using different electrolyte solution including sodium chloride (NaCl) and sodium sulphate (Na2SO4) on the surface roughness (Ra) and material removal rate (MRR).Generally increasing in machining parameter (concentration of solution, current and voltage) lead to increase in (MRR) and (Ra).